2022
DOI: 10.1101/2022.04.29.490087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybridization drives mitochondrial DNA degeneration and metabolic shift in a species with biparental mitochondrial inheritance

Abstract: Mitochondrial DNA (mtDNA) is a cytoplasmic genome that is essential for respiratory metabolism. While uniparental maternal mtDNA inheritance is most common in animals and plants, distinct mtDNA haplotypes can coexist in a state of heteroplasmy, either because of paternal leakage or de novo mutations. MtDNA integrity and the resolution of heteroplasmy have important implications, notably for mitochondrial genetic disorders, genome evolution and speciation. However, knowledge on the factors driving heteroplasmy … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(177 reference statements)
0
0
0
Order By: Relevance
“…W. Taylor, 1986). Evidence seems mixed on whether recombination occurs readily over organismal (as opposed to evolutionary) timescales, with some studies observing extensive recombination (Hénault et al, 2022;Sena et al, 1986) and some with little observed (Y.-W. Wang et al, 2023). Of course, the observation of recombination will depend on many features including species and the extent of heteroplasmy (as in plants, above).…”
Section: Specific Strategies Across Eukaryotesmentioning
confidence: 99%
“…W. Taylor, 1986). Evidence seems mixed on whether recombination occurs readily over organismal (as opposed to evolutionary) timescales, with some studies observing extensive recombination (Hénault et al, 2022;Sena et al, 1986) and some with little observed (Y.-W. Wang et al, 2023). Of course, the observation of recombination will depend on many features including species and the extent of heteroplasmy (as in plants, above).…”
Section: Specific Strategies Across Eukaryotesmentioning
confidence: 99%